Anatomic-like polyethylene insert could improve knee kinematics after total knee arthroplasty — A computational assessment - Liu, Yu-Liang; Lin, Kun-Jhih; Huang, Chang-Hung; Chen, Wen-Chuan; Chen, Chih-Hui; Chang, Tsung-Wei; Lai, Yu-Shu; Cheng, Cheng-Kung (Clinical biomechanics (Bristol), 2011)
Deficiencies in contemporary posterior crucitate retaining knee included inadequate femoral rollback and insufficient tibial rotation. Current study attempted to restore normal femoral rollback and tibial rotation to facilitate in knee flexion/extension and to achieve appropriate posture at deep knee bending after total knee arthroplasy by mimicking the morphology of convexly lateral tibial plateau of intact knee. Computational simulation was utilized to analyze motion of three-dimensional knee models, including intact, traditionally symmetrical posterior crucitate retaining and newly anatomic-like posterior crucitate retaining knees. Solid bones, attachments of ligaments and tendons of simulation models were reconstructed by magnetic resonance images of the subject. According to the representative literature, the distal femur was modeled to rotate about the specific axes and the motion of the proximal tibial was unconstrained except for the flexion/extension. Movements of the medial/lateral condyles and tibial rotation were recorded and analyzed. The newly anatomic-like posterior crucitate retaining knee improved the posterior movement of lateral condyle and tibial internal rotation significantly during full range of flexion. Compared with traditionally symmetrical posterior crucitate retaining knee, the improvements displayed by newly developed posterior crucitate retaining knee in posterior movement of lateral condyle and tibial internal rotation were 11.2 mm and 9.3° at full flexion, respectively. The newly anatomic-like posterior crucitate retaining knee demonstrated that mimicking the morphology of convexly lateral tibial plateau can be expected to restore normal knee kinematics.